Mucosal innervation of the pig small intestine. A preliminary report. - Brehmer, Axel; Schrödl, Falk; Neuhuber, Winfried (Biogenic Amines, 1997)
The carbocyanine tracer DiI was applied into single villi of the fixed small intestine of pigs. After incubation of several months, labelled nervous elements were found in the plexus mucosus and the plexus muscularis mucosae as well as in the ganglionated nerve networks: the inner and outer submucous and the myenteric plexus. Both dendritic and adendritic neurons could be identified. The results indicate that neurons of all three ganglionated plexuses of the pig small intestine are integrated in mucosal function and, that their axons travel through non-ganglionated plexuses before reaching the mucosa.
Keywords: DiI; Enteric nervous system; Mucosal plexus; Neuron; Plexus muscularis mucosae